Biofortification in Palm Oil Based on Saponin Nanotechnology: Innovation in Nutritional Stability, Antioxidants and for Functional Quality - Sapto Priyadi; H. Haryuni; R. Soelistijono; Siti Mardhika Sari (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
Palm oil is the world's main vegetable oil commodity and significantly contributes to the food industry. However, challenges related to the low content of certain nutrients and susceptibility to lipid oxidation are major issues that affect product quality. Fortification technology is an innovative solution to improve palm oil's nutritional value and oxidative stability. This article aims to evaluate the development of modern technology in palm oil fortification, including the addition of vitamin A, vitamin E, bioactive compounds, and the use of natural and synthetic antioxidants. Various methods, such as microencapsulation, nanotechnology, and biofortification techniques, are discussed in the context of their effectiveness in maintaining nutritional stability, preventing lipid oxidation, and extending product shelf life. This review highlights the challenges of implementing fortification technology, including technical and regulatory aspects in the food industry. The results of the review indicate that fortification technology improves nutritional quality and the oxidative stability of palm oil, thus supporting the development of healthier and more value-added food products. The implementation of vitamin A and E fortification with nanotechnology is expected to be able to answer global nutritional challenges and increase the competitiveness of the palm oil industry in the international market.